How amazing music therapy in counseling for millennials - Situmorang, Dominikus David Biondi (COUNS-EDU: The International Journal of Counseling and Education, 2018)
Most of millennials college students in Indonesia still think that undergraduate thesis is a terrifying final project. In the process of making the undergraduate thesis, they often do something non-productive, like procrastinating doing it and avoiding their supervisors. This excessive academic anxiety toward undergraduate thesis could lead them to do something irrational, e.g. suicide. As one of college’s internal agents of change, psychologists or educational counselors are expected to overcome the problem which frequently happens every year by giving the students an intervention in accordance with their interests and needs as millennials. Music, as one of millennials’ essential needs, can be used as an alternative to therapeutic healing medium. Conventional counseling strategy that has been conducted all this time, shows only ineffective result. That is why it is needed to be changed into modern approach that is more effective in reducing academic anxiety of the millennials college students, which is integrative approach through music therapy intervention in counseling.